2015
DOI: 10.1002/anie.201504318
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Production of Universal Blood by Structure‐Guided Directed Evolution of Glycoside Hydrolases

Abstract: Coming closer to a vision: Directed evolution has been applied to a glycoside hydrolase for increased activity in the selective cleavage of A- and B-antigens from linkages on red blood cell surface glycans. The results are a major step forward in the challenging endeavor of producing universal blood

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
(35 reference statements)
0
2
0
3
Order By: Relevance
“…For instance, fibrinolytic enzymes are used clinically as thrombolytic agents to treat myocardial infarction, asparaginase and arginine deaminase are used to treat leukemia and solid tumors, and α- and β-galactosidases are used to treat lysosomal storage disease [ 40 ]. Moreover, naïve or structure-guided directly evolved glycohydrolases have been tested in trials to remove sugar residues from the surface of erythrocytes to obtain universal blood [ 41 ]. Supplementary Table S4 presents, a list of predicted P. variabilis enzymes for which counterparts are used in the treatment of rare metabolic diseases, cancer, and for experimental blood production and organ transplantation.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, fibrinolytic enzymes are used clinically as thrombolytic agents to treat myocardial infarction, asparaginase and arginine deaminase are used to treat leukemia and solid tumors, and α- and β-galactosidases are used to treat lysosomal storage disease [ 40 ]. Moreover, naïve or structure-guided directly evolved glycohydrolases have been tested in trials to remove sugar residues from the surface of erythrocytes to obtain universal blood [ 41 ]. Supplementary Table S4 presents, a list of predicted P. variabilis enzymes for which counterparts are used in the treatment of rare metabolic diseases, cancer, and for experimental blood production and organ transplantation.…”
Section: Resultsmentioning
confidence: 99%
“…The real challenge is to devise mutagenesis strategies that reliably generate high-quality mutant libraries that require minimal screening (bottleneck of directed evolution). We and other researchers have previously used reduced amino acid alphabets in SM at sites lining the binding pocket (CASTing), employing iterative saturation mutagenesis (ISM) if necessary, but it was not routinely clear which and how many amino acid building blocks should be chosen. , In the preceding study, we showed that triple-code saturation mutagenesis (TCSM) is particularly efficient for manipulating the stereoselectivity of limonene epoxide hydrolase (LEH). This approach utilizes three properly chosen amino acids (in addition to WT) as building blocks in SM at a large randomization site lining the enzyme’s binding pocket.…”
Section: Introductionmentioning
confidence: 99%
“…Yakın geçmişe kadar eritrosit yüzeyindeki A ve B antijenlerinin enzimatik etki ile elimine edilip O grubunda evrensel eritrosit konsantresi elde edilmesi yada A ve B antijenlerinin yanı sıra eritrosit yüzeyin-deki diğer antijenik yapılarında maskelenmesi ile antijenik özelliği taşımayan eritrosit konsantrelerinin transfüzyonu hedeflenmiş durumdaydı (3,4,(6)(7)(8)(9)(10)(11)(12) . Bir yandan bu yöndeki çalışmalar devam ederken yeni bir çözüm yolu olarak ayrı ayrı çalışmalarla olsa da birleştiğinde hedefi laboratuvar ortamında eritrosit konsantrelerinin üretimi olan çalışmalar da dikkati çekmektedir.…”
Section: A Evrensel Eritrosit Konsantreleriunclassified
“…Yakın tarihte Withers ve ark. (4) yürüttüğü çalışmada gen mutagenezi ile daha stabil ve aktif glikozid hidrolazlardan yararlanarak özellikle A antijenlerinin eritrosit yüzeyinden başarılı şekilde uzaklaştırdıklarını gös-termişlerdir.…”
Section: A1 "A" Ve "B" Antijenlerinin Enzimatik Yıkımıunclassified
See 1 more Smart Citation